Blood–brain barrier breakdown in reversible cerebral vasoconstriction syndrome: Implications for pathophysiology and diagnosis. Issue 3 (20th March 2017) - Lee, Mi Ji; Cha, Jihoon; Choi, Hyun Ah; Woo, Sook‐Young; Kim, Seonwoo; Wang, Shuu‐Jiun; Chung, Chin‐Sang
Abstract : Objective: Diagnosis of reversible cerebral vasoconstriction syndrome (RCVS) is currently based on luminographic findings of vasoconstriction. In addition to vasoconstriction, the blood–brain barrier (BBB) breakdown has been postulated as a central mechanism of RCVS. Our aim was to document BBB breakdown in patients with RCVS and its role for the pathophysiology‐based diagnosis of RCVS. Methods: We prospectively recruited 72 consecutive patients with thunderclap headache who did not have aneurysmal subarachnoid hemorrhage from April 2015 to July 2016 at the Samsung Medical Center. Based on the International Classification of Headache Disorders–3 beta criteria and neuroimaging, patients were classified as having RCVS (n = 41; "definite" in 29 imaging‐proven patients and "probable" in 12 imaging‐negative patients), other secondary causes (n = 7), and thunderclap headache of undetermined cause (n = 24). BBB breakdown was evaluated using contrast‐enhanced fluid‐attenuated inversion recovery magnetic resonance imaging. Results: BBB breakdown was documented in 20 (69.0%) patients with definite RCVS, 3 (25.0%) patients with probable RCVS, and none with other secondary causes. BBB breakdown was present in RCVS patients with (n = 4) and without (n = 19) concomitant posterior reversible encephalopathy syndrome. In patients with RCVS, the extent of BBB breakdown was independently associated with neurological complications (multivariate odds ratio = 1.48 per 1 territorial increase, 95% confidence interval = 1.04–2.12, adjusted p = 0.032). Three (12.5%) patients with thunderclap headache of undetermined cause were newly classified as having RCVS by the presence of BBB breakdown. Interpretation: This is the first study to show BBB breakdown in patients with RCVS. This finding might broaden our understanding of the pathophysiology and clinical spectrum of RCVS. Ann Neurol 2017;81:454–466